POSIBILITIES OF USING DOCKER CONTAINERS - Žogots, Dainis; Ežmale, Sandra (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Considering that in nowadays virtualization in various Information Technology (IT) systems is becoming more demanding, it is necessary to deeply understand the possibilities, advantages and risks of that kind of technologies. One of these virtualization tools is the Docker containers, which are becoming more convenient, faster, more popular and more profitable than virtual machines (VM). The aim of this work is to explore and analyze the possibilities of Docker containers and to evaluate the pros and cons of the given technology. Also determine when it is worth using Docker containers as virtualization tools for an IT system.